The Effectiveness of E-KTP Services at the Public Service Mall in Serang City - Dida Suhada Iskandar; Faria Ruhana; Karno Karno (Sean Institute, 2025)
This study aims to analyze the effectiveness of E-KTP services at the Public Service Mall (MPP) in Serang City by referring to the effectiveness indicators according to Ridwan and Sudrajat (2009), including service procedures, completion time, costs, facilities and infrastructure, employee competence, and service products. This study uses a qualitative approach with descriptive methods through observation, interviews, and documentation. The results of the study indicate that the effectiveness of E-KTP services at the MPP in Serang City has not been running optimally. There are several obstacles, such as the absence of a special SOP for MPP services, long waiting times even though documents are complete, the unavailability of biometric recording facilities, and the attitude of employees who are not polite. However, there are aspects that already reflect the principle of effectiveness, including: free service, the availability of adequate supporting facilities, and E-KTP service products that have met community expectations. In addition, supporting factors such as the existence of a legal basis for coordination between agencies, active community participation, and relatively good public facilities also strengthen the service. The main inhibiting factors include lack of socialization, limited electronic recording and queuing facilities, and lack of coaching for employee attitudes. The Serang City Government has made several improvement efforts such as procuring biometric recording devices, HR training, and developing an electronic queuing system to improve the quality of population administration services as a whole.